The glutamatergic neurons in the spinal cord of the sea lamprey: an in situ hybridization and immunohistochemical study. - Blanca Fernández-López (Public Library of Science (PLoS), 2012)
Glutamate is the main excitatory neurotransmitter involved in spinal cord circuits in vertebrates, but in most groups the distribution of glutamatergic spinal neurons is still unknown. Lampreys have been extensively used as a model to investigate the neuronal circuits underlying locomotion. Glutamatergic circuits have been characterized on the basis of the excitatory responses elicited in postsynaptic neurons. However, the presence of glutamatergic neurochemical markers in spinal neurons has not been investigated. In this study, we report for the first time the expression of a vesicular glutamate transporter (VGLUT) in the spinal cord of the sea lamprey. We also study the distribution of glutamate in perikarya and fibers. The largest glutamatergic neurons found were the dorsal cells and caudal giant cells. Two additional VGLUT-positive gray matter populations, one dorsomedial consisting of small cells and another one lateral consisting of small and large cells were observed. Some cerebrospinal fluid-contacting cells also expressed VGLUT. In the white matter, some edge cells and some cells associated with giant axons (Müller and Mauthner axons) and the dorsolateral funiculus expressed VGLUT. Large lateral cells and the cells associated with reticulospinal axons are in a key position to receive descending inputs involved in the control of locomotion. We also compared the distribution of glutamate immunoreactivity with that of γ-aminobutyric acid (GABA) and glycine. Colocalization of glutamate and GABA or glycine was observed in some small spinal cells. These results confirm the glutamatergic nature of various neuronal populations, and reveal new small-celled glutamatergic populations, predicting that some glutamatergic neurons would exert complex actions on postsynaptic neurons.